Benin : Sixth Review under the Extended Credit Facility Arrangement, and Request for Augmentation of Access-Press Release; Staff Report; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Benin's Sixth Review Under the Extended Credit Facility (ECF) Arrangement, and Request for Augmentation of Access. Program implementation continues to be strong, with all end-December 2019 quantitative performance criteria and the structural benchmarks under review being met. Economic activity is expected to decelerate sharply in 2020 due to the coronavirus disease 2019 pandemic. The authorities have prepared a response plan of 1.7 percent of gross domestic product (GDP) to contain health risks and support the economy. As a result of the projected revenue shortfall and the new measures, the 2020 fiscal deficit is revised upward to 3.5 percent of GDP. The authorities' policies under the ECF-supported program are substantially adapted to cope with the health and economic emergency. The IMF staff supports the completion of the sixth review under the ECF-supported arrangement. Staff also supports the request for an augmentation of access equivalent to 61.4 percent of quota to address larger financing needs.